2018
DOI: 10.1007/s12011-018-1500-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Acute Exercise Until Exhaustion on the Serum and Urinary Concentrations of Cobalt, Copper, and Manganese Among Well-Trained Athletes

Abstract: The current information about the effect of physical exercise on the body concentrations of several minerals is still limited, both in the acute (short-term) and adaptive (long-term) responses. So, this manuscript aims, on the one hand, to assess the possible differences on basal levels of cobalt (Co), copper (Cu), and manganese (Mn) concentrations in serum and urine between athletes and sedentary participants and, on the other hand, to evaluate the effect of an acute progressive physical exercise until volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Serum Co concentration was similar in both groups, but urinary concentration was significantly higher in CG than AG. These results are similar to those found by Muñoz et al (2019), also in high-level athletes, indicating that they could be due to an adaptive process to maintain normal values in serum and avoid a deficit of the element that could have negative consequences for the maintenance of erythropoiesis [12].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Serum Co concentration was similar in both groups, but urinary concentration was significantly higher in CG than AG. These results are similar to those found by Muñoz et al (2019), also in high-level athletes, indicating that they could be due to an adaptive process to maintain normal values in serum and avoid a deficit of the element that could have negative consequences for the maintenance of erythropoiesis [12].…”
Section: Discussionsupporting
confidence: 89%
“…The high serum Mn concentration found at the start of the study, but not at the end, in AG participants, is similar to other studies and could also be caused by a possible iron deficiency in athletes [10, 12, 13], a fact that would increase Mn absorption, as indicated by Park et al (2013) [27] or a decrease in urinary elimination in AG. However, it is interesting to highlight that at the end of the study the serum concentration of Mn in the AG is similar to those of the CG, accompanied by a significant increase in urinary elimination, which would reveal a possible renal adaptation with training.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Data on the impact of sports activity on manganese levels is limited. 38 According to the WHO 2016 diabetes country profile, Saudi women were among those with the highest prevalence of physical inactivity in the world at 67.7%. 2 Scientific evidence has confirmed that physical activity is directly related to the trace element concentration in women's toenails.…”
Section: Discussionmentioning
confidence: 99%